## Active forum topics

- Eliminate the Arbitrary Constants
- Law of cosines
- Maxima and minima (trapezoidal gutter)
- Special products and factoring
- Integration of 4x^2/csc^3x√sinxcosx dx
- application of minima and maxima
- Sight Distance of Vertical Parabolic Curve
- Application of Differential Equation: Newton's Law of Cooling
- Minima maxima: a²y = x⁴
- Trim and stability

## New forum topics

- Integration of 4x^2/csc^3x√sinxcosx dx
- Maxima and minima (trapezoidal gutter)
- Special products and factoring
- Newton's Law of Cooling
- Law of cosines
- Can you help me po to solve this?
- Eliminate the Arbitrary Constants
- Required diameter of solid shaft
- Differentiate trigonometric function
- Integration $\displaystyle \int \sec 2x ~ dx$

## Recent comments

- Mali po ang equation mo…3 days 6 hours ago
- $x$ is the location where…3 days 17 hours ago
- In double integration method…1 week 1 day ago
- Maayo, salamat sa imong…2 weeks 3 days ago
- 24 ft during the 10th second…2 weeks 3 days ago
- The differentiation you need…2 weeks 4 days ago
- Obtain the differential…2 weeks 4 days ago
- Thank you for sharing your…2 weeks 4 days ago
- Based on the differentiation…1 week 1 day ago
- Given that $x + y + xy = 1$,…1 week 1 day ago

## X= the square root of 2

X= the square root of 2

Simplify the given equation

1/x + 1/(x+2)=1

=>(( x+2) + x )/(x (x+2)) =1

=>(2x+2)/x(x+2)=x(x+2)/x(x+2)

=>2x +2=x^2+2x

=>x^2+2x-2x=2

=>x^2=2

Thus X= the square root of 2 ans.

To verify the answer substitute the value of x=the square root 2 from the given equation if it satisfies equals to 1

Using the calculator by typing the equation using Alpha X and Shift solve it will gives you an answer x= 1.414213562 which is the value of square root of 2.

## (1/x) + (1/(x+1)) = 1

(1/x) + (1/(x+1)) = 1 multiply by (x * (x+1))

(X+1) + x = x(x+1)

2x + 1 = ×^2 + x

x^2 - x - 1 = 0

x^2 - x = 1

x^2 - x + (1/2)^2 = 1 + (1/2)^2

(x - (1/2))^2 = ( 5/4 )

x - (1/2) = sqrt ( 5/4 )

x = (1/2) +- ((sqrt( 5 ))/2)

X1 = (1 + sqrt ( 5 ))/2

X2 = (1 - sqrt ( 5))/2

## +sqrt2 , -sqrt2

+sqrt2 , -sqrt2

## $\(\frac{1}{x} + \frac{1}{x+2

$$ \begin{eqnarray}

\frac{1}{x} + \frac{1}{x+2} &=& 1\\

(x + 2) + x &=& x(x+2) \\

2x + 2 &=& x^2 + 2x\\

x^2 &=& 2\\

x &=& \boxed{\pm \sqrt{2}}

\end{eqnarray} $$